Vegetable based nutri-garden for household food and nutrition security - Shuba, Kumari; Mukherjee, Anirban; Kumar, Ujjwal; Mishra, J S (Indian Horticulture, 2020)
There is widespread poverty, food insecurity and under-nutrition in India. The household level data on calorie intake indicates that the average calorie consumption among population in India is declining over the last twenty years. Considering the parameters of economic and social development, India’s undernourished population is continually on the rise and the situation has worsened with the spiralling inflation witnessed with regard to food prices. Even though with the government effort India is in a row towards achieving food security but still there is a large population suffering from undernourishment, and starvation. So the concern for nutritional security is the need of the hour.